A mobile application to support and strengthen maternal health services: case of Nairobi - Odwako, Vincent Anyanje (iLabAfrica, 2014)
In developing countries like Kenya, many deaths are attributed to infectious diseases and complications of pregnancy and childbirth. Men and women don’t have access to safe, effective, affordable and acceptable methods of fertility regulation. Most of the information pertaining maternal health services found on websites is too general and that not so many people have access to the internet. Such information is also found in health journals at unaffordable fee. On the other hand, health consultants charge exorbitant amounts of money to provide maternal health services and care. Also, women forget or ignore to go for the recommended antenatal checkups posing a risk to them and the unborn child. Healthcare professionals from Jacaranda health participated in the research through questionnaires and interviews so as to provide a more holistic picture in the area of maternal health. Project testing and evaluation score form was used to test the developed application on areas of functionality, usability, performance and integration. The purpose of this research was to support and strengthen maternal health services and care using mobile phones in Kenya. Therefore, a solution to access maternal health services and care was offered on one’s finger tips. This was a project to improve life and access to information via the mobile phone. The application provides all round information on maternal health services and has a discussion forum to boost collaboration between health practitioners. The application also has SMS functionality to remind pregnant women to go for antenatal checkups as well as provide health related campaigns and awareness. The test results of the developed application indicated that users felt that the system was able to meet their requirements effectively. The application was accepted by medical professionals at Jacaranda health since it was able to meet most of their needs. The application is useful for the general public, people living with HIV and AIDS, health workers and treatment activists.
A dissertation submitted in partial fulfillment of the requirements for the Degree of Master of Science in Mobile Telecommunications and Innovation